First assessment on the influence of wind farms and high-voltage networks on ruddy-headed goose Chloephaga rubidiceps migration in Patagonia, Argentina - Pedrana, Julieta; Gorosabel, Antonella; Pütz, Klemens; Bernad, Lucía (Polar Biology, 2023)
Ruddy-headed goose Chloephaga rubidiceps has a migratory population that overwinters mainly in the Pampas region, Argentina, and breeds in Southern Patagonia. This population has decreased considerably, with less than 800 individuals remaining to date. We conducted the first assessment on the influence of environmental and anthropogenic-impact (wind farms and high-voltage networks) variables on ruddy-headed goose migration pathways across the Patagonian coast by applying kernel density analyses and statistical procedures. We used satellite tracking data obtained from six ruddy-headed geese during their migration pathways between 2015 and 2018. Five core distribution areas were identified during migration. During autumn migration, core areas were associated with high primary productivity and low elevation areas, while during spring migration they were located in the proximity of watercourses and waterbodies. We found that more than 30% of the grid cells included in the influence area of high-voltage networks overlapped with high-density areas for ruddy-headed geese during both migrations. Around 30% of the grid cells included in the influence zone of wind farms overlapped with high-density areas for ruddy-headed goose during autumn migration; while this applied to only 13% during spring migration. We highlight areas of high-risk along the distributional range of the species where large-scale patterns of collision mortality are likely to occur and mitigation measures should be prioritized. We suggest proactive measures that could mitigate future collisions with energy infrastructure because, given their threatened status, a few deaths may have a large effect on the small remnant population. EEA Balcarce Fil: Pedrana, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Pedrana, Julieta. Universidad Tecnológica Nacional. Facultad Regional Mar del Plata. Departamento de Medio Ambiente; Argentina Fil: Gorosábel, Antonella. Instituto Nacional de Tecnología Agropecuaria (INTA). ...